The Role of China’s Overseas Special Economic Zones in Economic Development - Elrashidy, Salah Eldin Mohamed Ibrahim (AUC Knowledge Fountain, 2016)
The Chinese overseas SEZs came to offer a courageous, interesting model of economic development that, if successful, will generate favorable economic outcomes that extend not only to the hosting county but also to the country providing the investment opportunity. Indeed, this model has demonstrated some miraculous results inside China, driving the economy to unprecedented altitudes of growth. Nevertheless, little evidence has been set forth to display the ability of Shenzhen model to stimulate similar triumphs outside of China. To prove its validity as an effective tool, rigorous investigation needs to be put in place to assess the performance of the Chinese overseas SEZs, and more importantly to verify their contribution to the economy of hosting countries, or otherwise it will only qualify as an ambitious strategy developed by China to pursue its foreign policy agenda. The Chinese model of overseas SEZs emerges as one of the promising initiatives that gains considerable reputation from its amazing success in China. However, to be able to give full credit to this model, evidence should demonstrate its feasibility in developing countries where it has been put into action and to ensure that the element of reciprocity of benefit between China and the hosting country exists. For that purpose, this study has worked to provide an answer to one major question: “Can China’s overseas SEZs stimulate economic development of host countries?” Within the framework of this major research question the dissertation has come to the conclusion that China's overseas SEZs are able to bring about significant outcomes to the host country only if they were fitted within a long-term, nationwide strategy of economic liberalization. I would assume that the benefits realized through SEZs, either static or dynamic, are, primarily, dependent on the host government’s determination and commitment. In fact, the miraculous performance of Shenzhen in China during early 1980s would not have been sustainable without the backing of her fellow SEZs and, certainly, the government’s adequate management of its Open Door policy back then. After all, a single, detached, unsupported SEZ can hardly stimulate economic growth, even if this SEZ was Shenzhen.